Hybrid DP-ABC for multi-objective long-term generation mix: Malaysia electricity supply industry case / Siti Mariam Mohd Shokri - Mohd Shokri, Siti Mariam (2018)
The recent issues of depletion in oil, severe gas shortage, increasing in fuel cost and the environmental impact has become major challenges for the Malaysian power sector. These have led Malaysia to find alternative resources to generate electricity. The problem of what the optimum future fuel mix strategy for Malaysia is critical for ensuring sustainability of supply. Here, the development of long-term optimal generation mix model considering various objective functions could be used by the government and power utility to determine optimum long-term generation mix that could ensure an efficient, secure and environmentally sustainable supply of energy. Moreover, the effects of economic and political constraints on Malaysia’s generation mix in this study could help the Malaysian government to optimally plan energy-related policies that could drive the optimum generation mix strategy. This study could also help investors in new generation capacity to make decisions regarding new investment plans. This approach includes a single objective model, a multi-objective model, an improved multi-objective model and a stochastic applied in improved multi-objective model. The research has been carried out by first developing the long-term single objective generation mix planning model using DP. Three different objectives of generation mix were optimized individually namely cost, emission and the power system’s reliability subjected to the constraints that gives view to utilities on the impact of technologies in generation mix through a different objective.